Comparison Between Charlson Comorbidity Index (CCI) and The American Society of Anesthesiologists Physical Status Classification (ASA) in Predicting Mortality in Geriatric Patients Undergoing Anesthesia at Dr Sardjito Hospital Yogyakarta - Nugroho, Ragil Catur; Sari, Djayanti; Sudadi, Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2026)
Background: Geriatric patients tend to have more comorbidities accompanied by a decline in physiological and cognitive function, which impacts perioperative outcomes. The combination of physiological dysfunction, especially changes in pharmacodynamics and pharmacokinetics of drugs, leads to several challenges in administering anesthesia. The Charlson Comorbidity Index (CCI) has been used to predict mortality based on comorbidity assessment. The American Society of Anesthesiologists (ASA) categorizes physiological status to estimate patient health based on anesthesia expert assessment. Increased CCI and ASA scores are known to have significant correlation to increased mortality in geriatric patients undergoing surgery.Objective: To compare the Charlson Comorbidity Index (CCI) and the American Society of Anesthesiologists (ASA) Physical Status Classification in predicting mortality in geriatric patients undergoing anesthesia at Dr. Sardjito Hospital, YogyakartaMethods: A retrospective observational study was conducted on all geriatric patients undergoing anesthesia procedures in the operating room of Dr. Sardjito Hospital, Yogyakarta, during the period of February-April 2021. Normality tests were performed using Kolmogorov-Smirnov. Bivariate analysis was conducted using the Chi-square test. A p-value of <0.05 was considered statistically significant. The predictive validity of CCI and ASA scores, as well as the optimal cutoff point for CCI scores, were evaluated using multivariate logistic regression analysis based on discrimination testing by observing the Area Under Curve (AUC) and the Hosmer-Lemeshow calibration test. Results: There was a significant association between CCI scores and mortality (OR 4.589; 95% CI 1.257-16.747; p=0.021). Meanwhile, no significant association was found between ASA and mortality in geriatric patients undergoing anesthesia